KESIAPAN SEKOLAH DALAM MENGIMPLEMENTASIKAN KURIKULUM MERDEKA MANDIRI BERUBAH DI SMPN 1 SUNGAI RUMBAI KABUPATEN DHARMASRAYA - Romalia, Romalia; Adripen, Adripen; Herlina, Elda (Hijri, 2024)
This research aims to: (1) reveal the readiness of teachers in implementing the Independent Mandiri Change Curriculum, (2) reveal the readiness of facilities and infrastructure in implementing the Independent Mandiri Change Curriculum. The research location is SMPN 1 Sungai Rumbai, Dharmasraya Regency. The research period is from February to August 2023. The subjects of this research are teachers and infrastructure. The instruments in this research are interview guidelines and documentation guidelines. Data collection techniques are interviews and documentation studies. The data validity guarantee techniques used are source triangulation and technical triangulation. The data analysis techniques used are: (1) Data reduction; (2) Presentation of data (3) drawing conclusions and verification. The results of this research show (1) Teachers' readiness to implement the independent independent curriculum has changed; (a) The teacher's readiness to increase understanding of the independent and changing curriculum structure is; taking part in online seminars, training with driving schools, workshops, studying with colleagues, driving teachers, and independent study on the Merdeka Teaching Platform (PMM); (b) Teacher readiness in creating and using teaching tools/modules starts from the teacher having Learning Outcomes (CP), analyzing CP, determining the Learning Goal Flow (ATP), and making assessments; (c) Teacher readiness in P5 activities starts from forming a team, identifying school readiness, determining dimensions, themes, time, and creating a Project module; (d) Teacher readiness in carrying out initial assessments/diagnostic assessments starts from the division of teacher duties, namely that cognitive diagnostic assessments will be carried out by subject teachers, while non-cognitive diagnostic assessments will be carried out by guidance and counseling teachers and homeroom teachers; (e) Teacher readiness in implementing differentiated learning in the form of conducting and analyzing diagnostic assessments; (2) Readiness of facilities and infrastructure; availability of textbooks for each subject, 1 book/student; availability of two computer laboratories capable of accommodating 2 study groups connected to the internet. Thus, the readiness of teachers and infrastructure really supports the implementation of the independent and independent change curriculum at SMPN 1 Sungai Rumbai.